Comparison of Equations of the VI Characteristics of an Electric Arc in Open Air - Andrea, Jonathan; Schweitzer, Patrick; Carvou, Erwann (Electrical contacts, 2019)
This paper presents a comparison of VI characteristics of an arc. Many VI characteristic equations can be found in papers on the subject, though they all vary slightly in form and are obtained through empirical processes. We will present a non-exhaustive list of these empirical equations and identify the one which is most suitable by comparing it with the result of an arcing VI characteristic measurement. This identification was made possible by calculating the absolute difference between measures and fitted equations. The subsequent data is presented in a radar plot.